Deeply virtual compton scattering in color dipole formalism - Machado,Magno V. T. (2007)
In this contribution we summarize recent investigations on the deeply virtual Compton Scattering (DVCS) within the color dipole approach. The color dipole cross section is implemented through the phenomenological saturation model. The role played by its QCD evolution and skewedness effects in the DVCS cross section are discussed. The results are compared with the recent H1 and ZEUS Collaborations data. The skewing factor, defined as the ratio of the imaginary parts of the amplitudes ImA(gamma*p ® g* p)/ImA(gamma*p ® gp) can be extracted from the data using recent DVCS and the inclusive inelastic cross section measurements at DESY-HERA. We report on this experimental extraction and compare the results to the theoretical predictions for NLO QCD and the color dipole approach.